Politicians' promotion incentives and bank risk exposure in China - Li Wang; Lukas Menkhoff; Michael Schröder; Xian Xu (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper shows that politicians' pressure to climb the career ladder increases bank risk exposure in their region. Chinese local politicians are set growth targets in their region that are relative to each other. Growth is stimulated by debt-financed programs which are mainly financed via bank loans. The stronger the performance pressure the riskier the respective local bank exposure becomes. This effect holds for local banks which are under some control of local politicians, it has increased with the release of stimulus packages requiring local co-financing and it is stronger if politicians hold chairmen positions in bank boards.
Keywords: G21; G23; H74; 330; Bank Lending; Bank Risk Exposure; Local Politicians; Promotion Pressure